Two new sympatric species of Eusarsiella (Ostracoda: Myodocopida: Sarsiellidae) from the Florida Keys with a morphological phylogeny of Sarsiellinae - Churchill, Celia K.c.; Ellis, Emily A.; Pique, Alannah E.; Oakley, Todd H. (Zootaxa, 2014)
We describe two new sympatric species of Sarsiellidae from coastal Florida, USA: Eusarsiella bryanjuarezi sp. nov. and Eusarsiella eli sp. nov. We also present a morphological character matrix and maximum likelihood phylogenetic analysis for Sarsiellinae based on original species descriptions, representing 139 sarsiellins (including E. bryanjuarezi and E. eli). While support values across the phylogeny are low, E. bryanjuarezi and E. eli form a sister group pair with 68 % bootstrap support. Our phylogeny also showed support for six other sympatric sister-species pairs, distributed across Sarsiellinae’s range, which may be candidates for the study of speciation and niche differentiation. Similar to other analyses of myodocopids, our Sarsiellinae phylogeny recovered only three monophyletic genera: Anscottiella, Cymbicopia, and Chelicopia, indicating that characters used in taxonomy may often be homoplasious. Because of our finding of multiple polyphyletic genera, including the two most speciose genera in the subfamily (Eusarsiella and Sarsiella, the type genus) Sarsiellinae is a strong candidate for taxonomic revision.